2015
DOI: 10.1016/j.coviro.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Origin, evolution and innate immune control of simian foamy viruses in humans

Abstract: Most viral pathogens that have emerged in humans have originated from various animal species. Emergence is a multistep process involving an initial spill-over of the infectious agent into single individuals and its subsequent dissemination into the human population. Similar to simian immunodeficiency viruses and simian T lymphotropic viruses, simian foamy viruses (SFV) are retroviruses that are widespread among non-human primates and can be transmitted to humans, giving rise to a persistent infection, which se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
(87 reference statements)
2
16
0
Order By: Relevance
“…Our results indicate that infection by the herpesviruses CMV, LCV and RRV and by the retrovirus SFV is frequent and often acquired early in life in the macaque population studied. These results are generally in keeping with published data (Chu et al, 1971;Ishida and Varavudhi, 1992;Ryan and Rose, 2013;Vogel et al, 1994;Calattini et al, 2006;Jones-Engel et al, 2007Muniz et al, 2015) although the macaque colony in Gibraltar was found to be CMV negative, for reasons not fully understood . Transmission is thought to occur via the oral route and/or through bites and scratches.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that infection by the herpesviruses CMV, LCV and RRV and by the retrovirus SFV is frequent and often acquired early in life in the macaque population studied. These results are generally in keeping with published data (Chu et al, 1971;Ishida and Varavudhi, 1992;Ryan and Rose, 2013;Vogel et al, 1994;Calattini et al, 2006;Jones-Engel et al, 2007Muniz et al, 2015) although the macaque colony in Gibraltar was found to be CMV negative, for reasons not fully understood . Transmission is thought to occur via the oral route and/or through bites and scratches.…”
Section: Discussionsupporting
confidence: 90%
“…FV replication is inhibited by IFN-α, -β, and -γ. Two possible escape mechanisms from the antiviral action of IFNs have been described for FVs: the low lysine content of the Gag protein conferring partial resistance to IFN-α in primary cells and the synthesis of an miRNA inhibiting response to IFN [27]; (3) most steps of the FV life cycle are sensitive to the action of major IFN-induced restriction factors, including the alpha isoform of tripartite motif-containing protein 5 (TRIM5α), apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC), interferon-induced 35 kDa protein (IFP35), TRIM19, and Tetherin [20,31]; (4) regarding the adaptive immune effectors, FV-virus specific T lymphocytes have not been described thus far. Neutralizing antibodies against cell-free FV are detected in most animal and human hosts.…”
Section: Summary Of Scientific Sessionsmentioning
confidence: 99%
“…FVs are naturally endemic to most non-human primates (NHPs), including New and Old World monkeys and apes, cats, cows, horses, tree shrews, sea lions, and bats (reviewed in [2,8,9]). In addition, endogenized copies of FV genomes were identified in sloths, the aye-aye, the Cap golden mole [10,11], cod [12], platyfish [12], zebra fish, and the coelacanth.…”
Section: Introductionmentioning
confidence: 99%